Simple strategies for teaching children at risk, K-5 - Stormont, Melissa; Thomas, Cathy Newman, 1957- (Corwin, 2014)
This reference covers the author's latest work and draws upon their field experiences within special education and psychology to offer K-5 teachers practical tools for building relationships with "at risk" children. Readers will discover simple strategies for developing students' academic aptitude and social behavior as well as how to identify who is at risk for failure and why